Covid 19 Pandemic-A Bane to Seeking Information in India (Medico Legal Update, 2020)
Right to seek information is a right deeply embedded into Article 19 of the Indian Constitution and whichgenerally cannot be suspended in the worst of the worst situations save exceptions. The right guaranteesIndian citizens to seek information from the public authorities on the touchstone of informed citizenry,greater and transparent access to information, accountability, and optimum use of limited fiscal resources.The recent impact of COVID -19 has not only shaken the basic edifice in India but has also weakened thecountries across the world in some or the other mode. In a way the pandemic has caused immense trench inthe economic as well as social well-being of the citizens.The Right to Information Act, 20051 was enacted by the Parliament in India with the aim to provide forsetting out the practical regime of right to information for citizens to secure access to information under thecontrol of Public Authorities. The basic objective of the Right to Information Act is to empower the citizens,promote transparency and accountability in the working of the Public Authorities, contain corruption, andmake our democracy work for the people in real sense.Therefore an attempt in this paper has been made to ascertain, whether the rights of citizen to seek informationin this great despondency time of Covid- 19 has been able to bolster or not. Weather the right to informationas guaranteed by the Indian Constitution is available to citizen irrespective of the pandemic situation.